Management of Spontaneous Rectal Perforation at Up-Coming Medical College Hospital: A Rare Occurrence - Singh, R.K. (Birat Journal of Health Sciences, 2017)
Spontaneous perforation of large bowel compare to small bowel is very uncommon and among them “spontaneous rectal perforation” is very rare cause of acute abdomen in surgical practice. The presentation of such entity is similar to any other cause of peritonitis & pre-operatively definite diagnosis remain a diagnostic dilemma and require an emergency surgical intervention to have the best outcome. We report a case of a 83 years male presented to our Emergency Department referred from B. P. Koirala Institute of Health Sciences with feature suggestive of peritonitis, hollow viscous perforation with evidence of free air under right dome of diaphragm in chest X-ray PA view. An emergency exploratory laparotomy was performed with provisional diagnosis of duodenal ulcer perforation as being commonest in this region with differential diagnosis of appendicular perforation or small bowel perforation with peritonitis. But on exploration no perforation was found in duodenum, small bowel, appendix and large bowel etc. Lastly with much difficulty the rectal perforation could be located while removing the plaques adhered to the rectal wall. Seeing such cases a surgeon should be aware of the possibility of this fatal disease despite rare incidence. It is very important to recognize such condition at an early stage because it carries high mortality if surgical intervention is not done at early stage. Intra-operatively too a thorough search should be made towards rectum if perforation is not found easily at other sites. Hence the better prognosis is with early surgical intervention; worst the prognosis with late intervention.Birat Journal of Health Sciences 2016 1(1): 87-90